Analisis Laporan Arus Kas untuk Menilai Kinerja Keuangan Pada PT Indofood Sukses Makmur Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Afrisah Putriani; Elfina Okto Posmaida Damanik; Johanes Wilfrid Pangihutan Purba (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Cash is a financial report that contains information on cash inflows and outflows from an entity during a certain period, to obtain information on receipt of cash disbursements, a cash flow statement is made. Companies must include a cash flow statement in their annual financial statements. Included in the analysis of financial performance using a cash flow statement is an analysis of the cash flow ratio. The purpose of this study was to determine the performance of the company PT Indofood as measured by using the cash flow ratio in measuring the financial performance of PT Indofood Sukses Makmur Tbk. The analytical method used is descriptive quantitative by looking at the cash flow statements and financial performance of PT Indofood Sukses Makmur Tbk. The population of financial statements at PT Indofood Sukses Makmur Tbk, sample financial statements for 2016-2020 with financial ratios, namely cash flow ratios, cash coverage ratios to interest, cash coverage ratios to current liabilities, capital expenditure ratios, total debt ratios and cash adequacy ratios Genre. From the results of the study it was concluded that the performance of PT Indofood Sukses Makmur Tbk according to the calculation of the financial cash flow ratio (AKO) with an average value of 0.38 < 1, the ratio of cash flow coverage to current liabilities (CKHL) with an average value of 0.57 < 1, Capital expenditure ratio (PM) with an average value of 0.24 < 1, total debt ratio (TH) with an average value of 0.19 < 1, cash flow adequacy ratio (KAK) with an average value of 0.012 < 1 is not good, which means that the performance of the company PT Indofood Sukses Makmur Tbk cannot manage the existing cash flow to be able to generate cash flow properly in order to meet its short-term obligations and current liabilities. The cash to interest coverage ratio (CKB) with an average value of 17,595 > 1 is good, which means very good because the cash can cover the interest costs of PT Indofood Sukses Makmur Tbk and can pay it directly without having to sell assets.